I HAVE A DREAM! ON THE PERCEIVED LIMITS AND MAGINED POSSIBILITIES OF BODY MONITORING - Berg, Martin (AoIR Selected Papers of Internet Research, 2015)
There is a growing market for, and use of, digitally mediated body monitoring and self- tracking devices – technologies that measure and report on everything from how fast you run, and what mood you are in, to devices that measure sleep patterns and pulse. The development of new social and digital body monitoring technologies has profound implications for the ways people experience both their bodies and the environments in which they live, and raises practical and ethical questions about how the body can (or should) be monitored/quantified, and how people imagine their futures/ future bodies.